Clostridioides difficile Ribotype 027 (RT027) Outbreak Investigation Due to the Emergence of Rifampicin Resistance Using Multilocus Variable-Number Tandem Repeat Analysis (MLVA) - Kabała M; Gofron Z; Aptekorz M; Sacha K; Harmanus C; Kuijper E; Martirosian G (Infection and Drug Resistance, 2021)
Monika Kabała,1,* Zygmunt Gofron,1,* Małgorzata Aptekorz,1 Krzysztof Sacha,1 Celine Harmanus,2 Ed Kuijper,2 Gayane Martirosian1 1Department of Medical Microbiology Medical University of Silesia in Katowice, Katowice, Poland; 2Department of Medical Microbiology Leiden University Medical Center, Leiden, the Netherlands*These authors contributed equally to this workCorrespondence: Gayane MartirosianDepartment of Medical Microbiology Medical University of Silesia in Katowice, 18 Medyków str, Katowice, 40-752, PolandEmail gmartir@sum.edu.plObjective: The aim of this study was Clostridioides difficile outbreak investigation due to the emergence of rifampicin resistant ribotype 027 (RT 027) fecal isolates from patients of Polish tertiary care hospital between X. 2017 and II. 2018 using multilocus variable tandem repeat analysis (MLVA).Materials and Methods: Twenty-nine C. difficile fecal isolates from patients of tertiary care hospital in Southern Poland were ribotyped and analyzed by MLVA. Multiplex PCR (mPCR) for genes encoding GDH (gluD), toxins A (tcdA)/ B (tcdB), 16S rDNA and binary toxin genes (ctdA and ctdB) was performed. The antibiotic susceptibility profile was determined by E-test.Results: The A, B and binary toxins encoding genes were detected in all 29 C. difficile strains which were sensitive to metronidazole, vancomycin and were resistant to erythromycin, clindamycin, and moxifloxacin; resistance to imipenem demonstrated 97%, to rifampicin – 45% isolates. C. difficile strains could be grouped by MLVA into 5 distinct clusters, and the largest cluster II contains 16 strains. The comparison of rifampicin GM MIC of cluster II (n=16 strains) with all others (n=13) showed that strains from clusters I, III, IV and V possessed significantly (p < 0.005) higher GM MIC and were more resistant to rifampicin.Conclusion: MLVA analysis proved transmission and recognized outbreak due to multidrug-resistant RT 027 C. difficile among patients of tertiary care hospital in Southern Poland. The reason for this is probably the widespread occurrence of spores in the hospital environment, which includes, among others, neglect of hygienic procedures and epidemic supervision. High resistance to imipenem (97%) and to rifampicin (45%) among C. difficile RT 027 Silesian isolates is threatening and requires further studies to elucidate this phenomenon.Keywords: Clostridioides difficile, epidemiology, MLVA, RT 027, rifampicin resistance